New Genes in Drosophila Quickly Become Essential - Chen, Sidi (Science, 2010)
To investigate the origin and evolution of essential genes, we identified and phenotyped 195 young protein-coding genes, which originated 3 to 35 million years ago in Drosophila. Knocking down expression with RNA interference showed that 30% of newly arisen genes are essential for viability. The proportion of genes that are essential is similar in every evolutionary age group that we examined. Under constitutive silencing of these young essential genes, lethality was high in the pupal stage and also found in the larval stages. Lethality was attributed to diverse cellular and developmental defects, such as organ formation and patterning defects. These data suggest that new genes frequently and rapidly evolve essential functions and participate in development.